EMISSION AND ATMOSPHERIC IMPACT OF A CUBAN REFINERY - Colás, J. A.; Díaz, M.; Álvarez, O.; Teuteló, R. (Revista de Engenharia Térmica, 2005)
In the processes of an oil refinery, considerable emissions of atmospheric pollutants are generated that produces hazard to mans health and the environment. In this study, the obtained results of the characterization of the gaseous emissions by chimneys of the furnaces and boilers of the refinery are presented. The sampling and analysis of SO2, NOX, CO, total suspended particles, and flow measurements were carried out. The aromatic hydrocarbons were determined by UV Spectroscopy. The model of dispersion of pollutants emitted by chimneys was executed using the software for the calculation of the gas concentration from continuous industrial sources following the methodology approved in the Cuban standards, according to the Berliand Model. We conclude that the combustion processes of the Refinery reflect a fault, given the particles emissions. The emissions of the furnaces and boilers exert negative impact or pressure on the atmospheric environment in the area.